Factors related to utilization and dropout from follow-up psychological services at the Rape Trauma Services in Iceland - Gyða Dröfn Hjaltadóttir 1991- (2017)
Psychological consequences of sexual assault can be serious and prolonged. However, only a portion of assault survivors utilize psychological services following the assault and a substantial part of those who utilize such services drop out of treatment prematurely. Few studies have been conducted to understand why this is and it is still unclear what factors affect utilization and dropout in psychological services among sexual assault survivors. The aim of the present study was to identify factors related to utilization and dropout in follow-up psychological services at the Rape Trauma Services (RTS) at the National Hospital in Iceland. Participants were 90 survivors of sexual assault who sought services in the years 2010 through 2014 and answered a service survey in 2015 and 2016. Data from medical records and a service survey was used for analysis in the study. The study found that prior or current substance abuse was significantly higher among participants who did not utilize services following sexual assault. Furthermore, results showed that individuals who were unpartnered were more likely to drop out of psychological treatment than those who were in a relationship or married. Participants implied that dissatisfaction with services and wanting to avoid dealing with the sexual assault affected utilization of services and dropout of treatment. The findings suggest that individuals with a prior or current substance abuse who are unpartnered and want to avoid dealing with the assault are at risk for not utilizing services or dropping out of treatment. It’s important to adapt services with these factors in mind. Sálrænar afleiðingar kynferðisofbeldis geta verið alvarlegar og langvarandi. Þrátt fyrir það sýna rannsóknir að aðeins hluti þolenda nýtir sálfræðiþjónustu í kjölfar ofbeldisins og brottfall úr sálfræðimeðferð er algengt á meðal þeirra sem hefja meðferð. Fáar rannsóknir hafa verið gerðar á þessu sviði og enn er óljóst hvaða þættir eru tengdir þjónustunýtingu og brottfalli meðal þolenda. Markmið ...